The Impact of COVID-19 on the Capital Structure of Listed Real Estate Firms and Analysis of Countermeasures: Evidence from China - Ma, Mingyi (2022)
The COVID-19 pandemic has severely affected global economic activity. This paper examines the impact of capital structure in the Chinese real estate sector during the COVID-19 pandemic. The results find that the COVID-19 pandemic have a negative impact on corporate capital structure, which negative impact is more pronounced for large-scale firms. In addition, the pandemic also have a negative impact on firms' cash, investment and enterprise value. Robustness tests also support this view. Finally, this paper also finds that the pecking order theory still has explanatory power for firm-level variables and leverage relationships even during the COVID-19 pandemic. This study provides insight into the capital structure of real estate firms in the post-pandemic period and helps to build sustainability and resilience in a volatile market.